MXSGD alleviates CsA-induced hypoimmunity lung injury by regulating microflora metabolism - Ye, Chun; Gao, Zi han; Bie, Zi-yi; Chen, Kai-qin; Lu, Fang guo; Wei, Ke (Frontiers in Immunology, 2024)
Context: Ma Xing Shi Gan Decoction (MXSGD) is a traditional remedy for treating lung injuries that was developed by the Typhoid and Fever School of Pharmaceutical Biology. It has antitussive and expectorant effects, anti-inflammatory, antiviral, regulates the body's immunity, etc. Aim: The aim of this study is to investigate whether MXSGD can ameliorate cyclosporine A (CsA)-induced hypoimmunity lung injury by regulating microflora metabolism. Methods: Establishment of a model for CsA-induced hypoimmunity lung injury. Using 16S rRNA high-throughput sequencing and LC-MS, the effects of MXSGD on gut flora and lung tissue microecology of mice with CsA-induced hypoimmunity were investigated. Results: MXSGD was able to preserve lung tissue morphology and structure, reduce serum inflammatory marker expression and protect against CsA-induced lung tissue damage. Compared to the model, MXSGD increased beneficial gut bacteria: Eubacterium ventriosum group and Eubacterium nodatum group; decreased intestinal pathogens: Rikenellaceae RC9 intestinal group; reduced the abundance of Chryseobacterium and Acinetobacter, promoted the production of Lactobacillus and Streptococcus, and then promoted the lung flora to produce short-chain fatty acids. MXSGD was able to enhance the expression of serum metabolites such as Americine, 2-hydroxyhexadecanoylcarnitine, Emetine, All-trans-decaprenyl diphosphate, Biliverdin-IX-alpha, Hordatin A and Ndemethyl mifepristone in the CsA-induced hypoimmunity lung injury model. Conclusion: MXSGD can restore gut and lung microbiota diversity and serum metabolite changes to inhibit inflammation, ameliorate CsA-induced hypoimmunity lung injury.